Development of an electrostatically assisted solvent extraction column - Steffens, Marc J. (Curtin University, 2011)
Solvent extraction (SX) is the only commercially viable hydrometallurgical separation and purification technique for a range of metals that allows high product throughput and consistently high recoveries. After over 50 years of commercial application, however, limitations inherent to the mechanical agitation used within the most widely used commercial SX contactor – the mixer-settler – have become apparent. It is now generally accepted that mechanical agitation results in regions of high shear within the mixer, which favours the formation of crud, non-uniform droplet sizes and the formation of numerous ultra-fine droplets. The other commercially used contactor, the pulse column, does not suffer from as many problems as the mixer-settler but it is not suitable for systems with slow kinetics.A promising alternative to these mechanically agitated solvent extraction contactors are electrostatically agitated solvent extraction (ESX) contactors. Bench-scale studies indicate that these contactors allow higher rates of mass transfer, excellent control of droplet size, and lower shear agitation than mechanically agitated contactors. There are also suggestions that the technique requires only a fraction of the power relative to that of mechanical agitation. Despite these promising attributes, a commercial application has not been achieved. This may be attributed to a poor understanding of electrostatically-assisted droplet dispersion over a range of commercially applicable solution properties, the designs of ESX contactors already proposed being unsuitable for scale-up and the performance of an ESX contactor never having been evaluated on a pilot-scale.To better understand electrostatically-assisted droplet dispersion, a dispersion study that allowed the measurement of dispersed droplet sizes was carried out over a range of commercially applicable solution properties. To develop an ESX contactor suitable for scale-up and industrial application, various types of electrostatic field conditions were evaluated and numerous electrode designs were developed and evaluated. Finally, to evaluate the performance of the ESX contactor on a pilot-scale, a pilot-scale ESX column was constructed and its performance was compared to that of a sieve-plate pulse column, which was refurbished for this purpose. In pursuing the first objective it was found that: •The viscosity of both the solvent and the PLS, and the interfacial tension affect the droplet size distribution generated by electrostatic dispersion largely by affecting the number of ultra-fine droplets that form. The solvent conductivity affects droplet dispersion by affecting the degree of interfacial polarisation of the droplet. • Electrostatic droplet dispersion occurs either via a necking or jetting dispersion mechanism. In ESX, droplet dispersion by necking is favourable as it impedes the formation of ultra-fine droplets. The predominance of one mechanism over the other is influenced by the viscosity of the PLS and solvent.In pursuing the second objective it was found that: • An individual electrostatic PLS disperser is not appropriate for an industrially applicable ESX column. • Droplet motion within an electrostatic field is influenced by the electric charge that droplets carry and also by the strength and frequency of the electrostatic field. Increases in the charge of the droplet favours droplet motion and agitation; increases in the frequency of the electrostatic field favours droplet oscillation; decreases in the frequency of the electrostatic field favours droplet zigzagging. • A horizontal rod electrode arrangement within a column type contactor was found to be the most appropriate design for scale-up because it allowed (1) good droplet dispersion and agitation, (2) adequate aqueous fluxes to be achieved, and (3) coalescence of any ultra-fine droplets that form.In pursuing the third objective it was found that: • An electrostatic field strength of 6.5 kV/cm and electrostatic field frequency of 40 Hz yielded the highest extraction of nickel metal from sulphate/chloride solution. Under these conditions, the fluxes achieved within the ESX column were comparable to those used in pulsed columns. This is particularly significant as it disproves the commonly perceived main limitation of electrostatic dispersion. • Concurrent operation of the ESX and sieve-plate columns, each with an aqueous flux of 37 m³/h/m², revealed that the metal extraction achieved within each column was comparable, with a height equivalent to a theoretical stage (HETS) of 3.30 m. This demonstrates that ESX columns can handle industrially applicable aqueous fluxes. Further improvements in the ESX column design promise enhanced results.